Effect of some environmental factors on the occurrence and distribution of Polychaeta Namalycastis indica (Southern, 1921) in the intertidal region of Shatt Al-Arab River Basrah Iraq - Al- Baghdadi, Nada M.; Sultan, Entesar N.; Abdullah, Abdul Aziz M. (Iraqi Journal of Aquaculture, 2022)
The current study was conducted on N. indica in three stations for the period from December 2017 to November 2018 (Al-Sharsh, Al-Salhiya and Al-Dweab), as samples were collected monthly. Some environmental factors were calculated, such as water temperature. The lowest water temperature was 12 °C during January and the highest temperature was 33 °C during July, both in Al-Salhiya station. The lowest value of salinity was 0.5‰ reached in April and November in Al-Sharsh station, while reached highest value ‰ 39.3 were recorded during July for Al-Dweab station, the light transmittance values ranged between (63-18) cm, recorded during July and November for Al-Salhiya and Al-Sharsh stations, respectively. As for the values of dissolved oxygen, it ranged between (12.1-5.1) mg/liter during August and May in the two stations. Al- Salhiya and Al-Sharsh, respectively. As for the bottom sediments of all the stations, they were alluvial with few and different percentages of sand and clay. The study showed that the studied environmental factors have an impact on the distribution and spread of this species within the horizontal and vertical sections in the tidal zone. The total density and density were measured within the horizontal distribution pattern in each station and the monthly total density ranges were 592-32 individuals/m2. The density of the three species was calculated within the horizontal distribution after dividing the area into three sections for each station. The results of the study indicated that there were significant differences at the level of P<0.05 for densities between the first and second different sections of N. indica, and there were significant differences between the first and third sections and between the second and third sections.